The Indochinese experience of the French and the Americans nationalism and communism in Cambodia, Laos, and Vietnam - Dommen, Arthur J. (Indiana University Press, 2001)
This is an essential book for anyone who wants to understand Vietnam and the people who fought against the United States and won.